The Role of Digital Banking in Leading Sustainable Economic Development - Alivia Meyrizka Utami; Mega Dwi Septivani (Telaah Bisnis, 2023)
This research examines the influence of Digital Banking on risk-taking and sustainability reporting in banks registered in Indonesia by analyzing panel data from 55 banks in Indonesia for the 2018-2021 period, thus collecting 220 observations. The research results show that Digital Banking is proven to reduce risk-taking and improve the quality of sustainability reporting of banks in Indonesia. Future research is expected to use data over a longer period and requires confirmation from independent parties who have expertise in this field so that they can combine quantitative and qualitative approaches so that the quality of the research is better. This research provides something new in examining the role of Digital Banking in making bank decisions as represented by risk and sustainability reporting.